CAUSALITY ANALYSIS OF CONCEPT UNDERSTANDING WITH CREATIVE THINKING ABILITY OF STUDENT TO SOCIAL CHANGE - Abednego - (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2021)
Creative thinking develops from students' potential; however, the level of ability to think creatively is different for every human being. Many scientists argue that the higher person's education level will be followed by the ability to think creatively. This statement's emergence stems from the idea that the higher a person's education is because the person receives more education and learning in quantity. From a different perspective, educators worry that the more knowledge a person gets from education and learning is mostly forgotten. It can be believed that not all learning can be understood by students. The conceptual approach applied in learning can help students understand various concepts. The quality of one's understanding can contribute to the ability to think creatively. The purpose of this study was to describe the causal relationship between conceptual understanding and creative thinking skills. The research data were obtained from 38 students through the pre-test and post-test of learning social change. The research data were analyzed using linear regression analysis. The results showed that the contribution of conceptual understanding to thinking creatively was 87%, and other factors influenced the rest. This study concluded that their causal relationship is significant between conceptual understanding and creative thinking skills.